2019
DOI: 10.1002/cphc.201900626
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐Thioether‐Containing Lipid Chains in Cationic Amphiphiles: Physicochemical Properties and Applications in Gene Delivery

Abstract: Cationic amphiphiles featuring two thioether functions in each lipid chain of bicatenar cationic amphiphiles are herein reported for the first time. The physico-chemical properties and transfection abilities of these new amphiphiles were compared with those of already reported analogues featuring either (i) saturated, (ii) unsaturated or (iii) mono-thioether containing lipid chains. The homogeneity of the series of new compounds allowed to clearly underscore the effect of bis-thioether containing lipid chains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It has been well established that p53 gene therapy activates proapoptotic machinery by provoking the G 0 /G 1 and G 2 /M cell cycle arrest. ,, With the aim of specifically incorporating a plasmid encoding for this tumor suppressor protein and restoring the apoptotic machinery in hepatocellular carcinoma, the anti-LDLr-tagged TH8S liposomes were used for the transfection of pCEP4-p53. Inhibition of cell proliferation, observed from the MTT Assay, showed that the tagged liposomes were able to deliver the plasmid efficiently in HepG2 and Huh7 cells ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well established that p53 gene therapy activates proapoptotic machinery by provoking the G 0 /G 1 and G 2 /M cell cycle arrest. ,, With the aim of specifically incorporating a plasmid encoding for this tumor suppressor protein and restoring the apoptotic machinery in hepatocellular carcinoma, the anti-LDLr-tagged TH8S liposomes were used for the transfection of pCEP4-p53. Inhibition of cell proliferation, observed from the MTT Assay, showed that the tagged liposomes were able to deliver the plasmid efficiently in HepG2 and Huh7 cells ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR (neat, cm Preparation of Maleimide-Functionalized Liposomes. The maleimide-functionalized tocopherol, TME (7), was dissolved in chloroform and mixed with chloroform solution of TH8S 19 maintaining 5 and 10 mol % amounts in two autoclaved Wheaton glass vials for each composition. For DOPE formulations, the helper lipid DOPE, dissolved in chloroform, was added in one of the vials of each group maintaining a molar ratio of 2:1 with respect to TH8S.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation